2023
DOI: 10.1111/iwj.14279
|View full text |Cite
|
Sign up to set email alerts
|

Platelet‐rich plasma influence on the sternal wounds healing: A meta‐analysis

Abstract: A meta‐analysis research was executed to appraise the effect of platelet‐rich plasma (PRP) on sternal wound healing (SWH). Inclusive literature research till April 2023 was done and 1098 interconnected researches were revised. The 11 picked researches, enclosed 8961 cardiac surgery (CS) persons were in the utilised researchers' starting point, 3663 of them were utilising PRP, and 5298 were control. Odds ratio (OR) and 95% confidence intervals (CIs) were utilised to appraise the effect of PRP on the SWH by the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…The third meta-analysis used as a comparison was Zhu et al (2023), this paper demonstrated that the use of PRP reduces the chances of DSWI and SWI after thoracic surgeries, however, the authors highlight the possibility of bias as the sample used was small and, in addition, the meta-analysis may present selection bias since other researches were not included.…”
Section: Literature Comparisonmentioning
confidence: 97%
“…The third meta-analysis used as a comparison was Zhu et al (2023), this paper demonstrated that the use of PRP reduces the chances of DSWI and SWI after thoracic surgeries, however, the authors highlight the possibility of bias as the sample used was small and, in addition, the meta-analysis may present selection bias since other researches were not included.…”
Section: Literature Comparisonmentioning
confidence: 97%